A LMI BASED CONTROL OF A THREE PHASE VOLTAGE SOURCE INVERTER CAPABLE TO OPERATE IN ISLANDED AND GRID CONNECTED MODES - Pena, Jose Carlos U. [UNESP]; Sampaio, Leonardo P.; Canesin, Carlos A. [UNESP]; IEEE (Ieee, 2015)
This paper introduces a strategy to control a three phase voltage source inverter used in distributed generation in microgrids scenario. In this context, the inverter should operate in grid connected and islanded modes. Moreover, the transitions between these two states should be made in a seamless fashion. The proposed strategy is based on a two control loops scheme. Each loop provides a component of the control input (duty cycles) by means of a state-feedback controller. In order to track sinusoidal references with minimum error and high disturbance rejection, state vector is expanded to include the states of a resonant controller. Furthermore, additional resonant components are considered to suppress low order harmonics in the injected current. Control Strategy also includes a criterion to manage the feedback patterns and the generation of reference and control signals. Two robust controllers are designed by means of Linear Matrix Inequalities based on discrete time state-space representations of each operation mode, typical disturbances and uncertainty due to grid impedance are considered. The obtained gains are accomplished by the two control loops and coordination scheme in order to guarantee the desired gain for each mode. Simulation results are presented to verify the validity of the proposed strategy.
Keywords: Islanded Operation; Linear Matrix Inequalities; Microgrid Inverter; Robust control